Peran Kepuasan Kerja dalam Memediasi Pengaruh Lingkungan Kerja Non Fisik dan Work-Family Conflict terhadap Motivasi - Paladita, Ida Bagus; Cahyadi, Irwan; Yuliana, Ika; Faerrosa, Lady; Marlini, Febria Nurmelia (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Employee motivation is essential in maintaining the productivity and performance of healthcare institutions, particularly in nursing services. However, motivation is often influenced by non-physical work environments and work-family conflict. This study aims to examine the effect of non-physical work environment and work-family conflict on motivation, with job satisfaction as a mediating variable. A quantitative associative approach was employed, involving 89 nurses from a public hospital in Lombok. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. The results revealed that both non-physical work environment and work-family conflict had a negative and insignificant effect on motivation. However, the non-physical work environment had a positive and significant effect on job satisfaction, while work-family conflict remained insignificant. Furthermore, job satisfaction demonstrated a positive and significant effect on motivation. The mediation analysis confirmed that job satisfaction successfully mediated the relationship between non-physical work environment and motivation but did not mediate the relationship between work-family conflict and motivation. These findings emphasize the central role of job satisfaction in enhancing employee motivation and suggest that creating a supportive non-physical work environment is more impactful than mitigating work-family conflict in the nursing context. This research contributes to organizational behaviour theory and offers practical recommendations for hospital management to improve internal work conditions that foster nurse motivation.